Pengembangan Karakter Holistik Peserta Didik Melalui Integrasi Social-Emotional Learning dalam Pendidikan Islam - Khoirul Umam Addzaky; Yazid Imam Bustomi; Muhammad Hafidz Khusnadin; Ilzam Hubby Dzikrillah Alfani (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The digital era has brought significant changes in the behavior patterns and character of the younger generation, marked by increasing cases of character degradation such as cyberbullying and decreasing empathy. This phenomenon demands a comprehensive approach in character development that is able to integrate cognitive, emotional, social, and spiritual aspects holistically. This research aims to develop a framework for the integration of Social-Emotional Learning (SEL) in Islamic education that can be implemented to shape the holistic character of students in the digital era. Using literature study method with content analysis technique, this research analyzes various literatures related to SEL and Islamic character education within the last 10 years. The results show the alignment between the core components of SEL and the fundamental values of Islamic education, where self-awareness correlates with the concept of muhasabah, self-management is in line with mujahadah an-nafs, social awareness and relationship skills reflect the value of ukhuwah and husn al-mu'asyarah, and responsible decision making is in line with the concept of maslahah. The developed integration framework has shown positive results in the transformation of learners' character, which is reflected in increased spiritual awareness, emotional maturity, social skills, and self-development. Implementation data showed an average 18% increase in learning achievement and a significant decrease in behavioral problems compared to the control group, indicating the effectiveness of this integrated approach in developing learners' holistic character